2014
DOI: 10.1016/j.nbd.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Megalencephalic leukoencephalopathy with subcortical cysts protein-1 modulates endosomal pH and protein trafficking in astrocytes: Relevance to MLC disease pathogenesis

Abstract: Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare leukodystrophy caused by mutations in the gene encoding MLC1, a membrane protein mainly expressed in astrocytes in the central nervous system. Although MLC1 function is unknown, evidence is emerging that it may regulate ion fluxes. Using biochemical and proteomic approaches to identify MLC1 interactors and elucidate MLC1 function we found that MLC1 interacts with the vacuolar ATPase (V-ATPase), the proton pump that regulates endosomal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…Specific V‐ATPase inhibition was shown to prevent TLR signaling dependent Salmonella typhimurium virulence (Arpaia et al, ) and a reduced TLR4 surface expression was accompanied by inhibited nitric oxide production in murine cells (Eswarappa et al, ), which is in accordance with our previous data showing ENV dependent nitrosative stress induction in oligodendroglial cells (Kremer et al, , ). On the other hand, V‐ATPase was also identified as target for the treatment of cancer, osteoporosis, and sepsis (Cotter et al, ; Forgac, ; Kartner & Manolson, ) and a contribution of V‐ATPase in different white matter pathologies such as the megalencephalic leukoencephalopathy with subcortical cysts (MLC) is suggested based on modulated intracellular pH‐homeostasis and protein trafficking in this disease (Brignone et al, ). Of note, an involvement of V‐ATPase in white matter homeostasis and brain function is further supported by observations on ATP6ap2.…”
Section: Discussionmentioning
confidence: 99%
“…Specific V‐ATPase inhibition was shown to prevent TLR signaling dependent Salmonella typhimurium virulence (Arpaia et al, ) and a reduced TLR4 surface expression was accompanied by inhibited nitric oxide production in murine cells (Eswarappa et al, ), which is in accordance with our previous data showing ENV dependent nitrosative stress induction in oligodendroglial cells (Kremer et al, , ). On the other hand, V‐ATPase was also identified as target for the treatment of cancer, osteoporosis, and sepsis (Cotter et al, ; Forgac, ; Kartner & Manolson, ) and a contribution of V‐ATPase in different white matter pathologies such as the megalencephalic leukoencephalopathy with subcortical cysts (MLC) is suggested based on modulated intracellular pH‐homeostasis and protein trafficking in this disease (Brignone et al, ). Of note, an involvement of V‐ATPase in white matter homeostasis and brain function is further supported by observations on ATP6ap2.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrated that in astrocytes exposed to hyposmotic stress MLC1 is translocated to the plasma membrane and then internalized by caveolar endocytosis to be sorted to recycling or degradation pathways ( Figure 3 ). By cell fractionation, immunofluorescence and electron microscopy analysis of rat primary astrocytes and human astrocytoma cells, MLC1 protein was detected in early endosomes (EEA1 + and Rab5 + ; Figures 3 and 4A,B ; Lanciotti et al, 2010 ; Brignone et al, 2014 ) and in Lamp-1 + organelles and multivesicular bodies ( Figure 4C ; Lanciotti et al, 2010 ; Brignone et al, 2014 ), but not, or at very low levels in Golgi apparatus and clathrin vesicles ( Lanciotti et al, 2010 ). More recently, we found that in unstimulated astrocytes MLC1 is abundantly expressed in the Rab11 + perinuclear storage/recycling compartment from which it is recruited back to the plasma membrane when cells are exposed to hyposmotic stress ( Figure 3 ; Brignone et al, 2014 ).…”
Section: The Puzzling Mlc1 Protein: Biochemical Features and Cellularmentioning
confidence: 99%
“…By cell fractionation, immunofluorescence and electron microscopy analysis of rat primary astrocytes and human astrocytoma cells, MLC1 protein was detected in early endosomes (EEA1 + and Rab5 + ; Figures 3 and 4A,B ; Lanciotti et al, 2010 ; Brignone et al, 2014 ) and in Lamp-1 + organelles and multivesicular bodies ( Figure 4C ; Lanciotti et al, 2010 ; Brignone et al, 2014 ), but not, or at very low levels in Golgi apparatus and clathrin vesicles ( Lanciotti et al, 2010 ). More recently, we found that in unstimulated astrocytes MLC1 is abundantly expressed in the Rab11 + perinuclear storage/recycling compartment from which it is recruited back to the plasma membrane when cells are exposed to hyposmotic stress ( Figure 3 ; Brignone et al, 2014 ). Cytoskeletal elements are involved in MLC1 intracellular trafficking since nocodazole treatment, which perturbs microtubule organization, hampers MLC1 accumulation in the Rab11 + endosomal recycling compartment in rat primary astrocytes ( Lanciotti et al, 2010 ).…”
Section: The Puzzling Mlc1 Protein: Biochemical Features and Cellularmentioning
confidence: 99%
See 2 more Smart Citations